A Business Proposal: Analisis Simulacra Romantisme Drama Korea - Anita Rosana (Universitas Nasional, 2022)
The Hallyu phenomenon is a Korean Wave phenomenon created due to the increasingly sophisticated mass media technology. Hallyu influences global civilization with various mass media products, including a Korean drama series with the theme of romance. The romance promoted in this Korean drama cannot be separated from what Jean Baudrillard calls Simulacra (false reality), which will later become a hyperreality when the pseudo-reality is believed to be more accurate than reality itself. The Korean drama series 'A Business Proposal' is an example of a drama that presents a form of utopian romance (pseudo-romantic). The concept of romanticism is built to give rise to a new concept of romanticism that is very different from the reality of romanticism. A Business Proposal presents a new concept of romanticism with an image as an ideal figure, aspects of romantic nature, hierarchical aspects of romanticism, aspects of romantic absurdity, and motivational aspects of romanticism. This study focuses on the analysis of the Korean drama A Business Proposal which was released in February 2022, in the perspective of Jean Baudrillard's Simulacra Theory, especially on the concept of romanticism or romantic relationships. The results show that the Korean drama A Business Proposal, wrapped in the main theme of romance, presents various kinds of utopian realities so that it can be said to be a drama full of avalanches of romantic Simulacra that creates a utopian romance. Fenomena Hallyu merupakan fenomena Gelombang Korea yang tercipta karena makin canggihnya teknologi media massa. Hallyu memengaruhi peradaban global dengan berbagai macam produk media massa, termasuk salah satunya serial drama Korea dengan mengusung tema romantisme. Romantisme yang diusung dalam drama Korea ini, tidak bisa lepas dari apa yang disebut oleh Jean Baudrillard sebagai Simulacra (realitas semu) yang kelak akan menjadi sebuah hiperrealita ketika realitas semu itu diyakini menjadi lebih riil daripada realita itu sendiri. Serial drama Korea A Business Proposal menjadi salah satu contoh drama yang menyajikan bentuk romantisme utopis (romantisme semu). Konsep romantisme dibangun sedemikian rupa sehingga memunculkan konsep romantisme yang baru yang berbeda jauh dengan realita romantisme. A Business Proposal, menyajikan konsep baru romantisme dengan citra sebagai figur ideal, aspek naturalitas romantisme, aspek hirarkis romantisme, aspek absurditas romantisme serta aspek motivasional romantisme. Penelitian ini menfokuskan pada analisa drama Korea A Business Proposal yang dirilis pada bulan Februari 2022, dalam perspektif Teori Simulacra Jean Baudrillard terutama pada konsep romantisme atau hubungan romantis. Hasil penelitian menunjukkan, drama Korea A Business Proposal dengan dibalut tema pokok romantisme, menyuguhkan berbagai macam realita utopis sehingga dapat dikatakan sebagai drama yang penuh dengan longsoran Simulacra romantisme yang menciptakan sebuah romantisme utopis.